Factors Affecting Social Media Advertising on Coffee Shops in Cabanglasan, Bukidnon - Tomegues, Baby Rose; Tigmo, Gilda Mae; Jomar, Vicente; Gonzales, Metonia (Journal of Interdisciplinary Perspectives, 2025)
This study addresses the lack of research on how social media advertising functions in rural coffee shops, particularly in Cabanglasan, Bukidnon. Its objective is to examine whether business profile characteristics— years in business, number of employees, and social media platforms used— relate to the effectiveness of social media advertising. A descriptive correlational design was used, and data were gathered from all licensed coffee shop owners in Cabanglasan who actively use social media. Results show that while most coffee shops are new, small-scale, and primarily rely on Facebook, these business profile factors do not significantly influence advertising effectiveness. Instead, owners emphasized that engaging content, consistent posting, and customer interaction are the primary drivers of online visibility and customer response. The study concludes that coffee shops should prioritize improving content quality and platform use strategies rather than relying on business size or longevity. These insights offer practical guidance for small rural businesses and contribute to the growing body of digital marketing research in non-urban settings.